A review study on blood in human coronary artery: Numerical approach. (April 2020) - Pandey, Rupali; Kumar, Manoj; Majdoubi, Jihen; Rahimi-Gorji, Mohammad; Srivastav, Vivek Kumar
Highlights: Critical review of the human heart is summarized that includes last ten years of research papers. Boundary conditions for the numerical studies are summarized in tabulated that will help to insight understanding for new researchers/readers working in this area. All the numerical schemes are listed with their governing equations as well as their advantages & disadvantages. Abstract: Computational fluid dynamics (CFD) study of blood flow in human coronary artery is one of the emerging fields of Biomed- ical engineering. In present review paper, Finite Volume Method with governing equations and boundary conditions are briefly discussed for different coronary models. Many researchers have come up with astonishing results related to the various factors (blood viscosity, rate of blood flow, shear stress on the arterial wall, Reynolds number, etc.) affecting the hemodynamic of blood in the right/left coronary artery. The aim of this paper is to present an overview of all those work done by the researchers to justify their work related to factors which hampers proper functioning of heart and lead to Coronary Artery Disease (CAD). Governing equations like Navier-stokes equations, continuity equations etc. are widely used and are solved using CFD solver to get a clearer view of coronary artery blockage. Different boundary conditions and blood properties published in the last ten years are summarized in the tabulated form. This table will help new researchers to work on this area.